Antimicrobial properties of white Malaga grape grown in Malaysia / Muhammad Azizi Samad … [et. al] - Samad, Muhammad Azizi; Adam, Nur Ain; Abdul Hadi, Siti Mastura; Omar, Nurul Hidayu; Mohd-Zain, Zaini (2012)
Grapes (Vitis vinefera) are usually produced and grow well in temperate countries. Many reports had shown that consumption of grape and parts of the fruit, especially the seeds, provides many health benefits. The purpose of this study was to explore the antimicrobial properties of grapes that are cultivated in Northern Malaysia. Samples consisting of fresh grape of White Malaga variety, prepared cordials of two varieties Red Opal and White Malaga; and dried grape ‘tea’ leaves were tested for their properties to inhibit growth of four species of bacteria, namely, Escherichia coli, Klebsiella pneumoniae, Streptocococcus aureus and Streptocococcus epidermidis. Disc diffusion test method was used to determine the ability of the samples to inhibit the growth of the bacteria. An experiment to determine the effect of storage of the samples at 4oC on their antimicrobial activity was also conducted. Results showed that fresh grape juice and both types of cordials were able to inhibit the growth of E. coli and K. pneumoniae, but their inhibitory activity against K. pneumoniae was lost upon refrigeration. By refrigerating the fresh juice, it was observe that the inhibitory activity against S. aureus and S. epidermidis was enhanced. The infused grape ‘tea’ leaves showed antimicrobial activity to S. epidermidis only after the refrigeration. This study therefore confirms that the White Malaga grape grown in tropical countries like Malaysia has antimicrobial properties that could be beneficial to human health, similar to many other previous reports.